2018
DOI: 10.15252/embj.201797368
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic activity‐induced glycolysis facilitates membrane lipid provision and neurite outgrowth

Abstract: The formation of neurites is an important process affecting the cognitive abilities of an organism. Neurite growth requires the addition of new membranes, but the metabolic remodeling necessary to supply lipids for membrane expansion is poorly understood. Here, we show that synaptic activity, one of the most important inducers of neurite growth, transcriptionally regulates the expression of neuronal glucose transporter Glut3 and rate-limiting enzymes of glycolysis, resulting in enhanced glucose uptake and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 91 publications
3
44
0
Order By: Relevance
“…2) [58]. Biosynthesis of macromolecules from glucose metabolites is critical to support key physiological processes behind proper brain growth and maturation; it has been shown, for example, that axon growth, synapse formation, and myelination rely critically on aerobic glycolysis [20,59,60]. Interestingly, aerobic glycolysis is predominant in the white matter compared to the gray matter, and it has been shown that glycolytic byproducts, such as lactate, are especially important for myelin production by oligodendrocytes [61,62].…”
Section: Glucose Requirements To Support Energy and Anabolic Demands mentioning
confidence: 99%
“…2) [58]. Biosynthesis of macromolecules from glucose metabolites is critical to support key physiological processes behind proper brain growth and maturation; it has been shown, for example, that axon growth, synapse formation, and myelination rely critically on aerobic glycolysis [20,59,60]. Interestingly, aerobic glycolysis is predominant in the white matter compared to the gray matter, and it has been shown that glycolytic byproducts, such as lactate, are especially important for myelin production by oligodendrocytes [61,62].…”
Section: Glucose Requirements To Support Energy and Anabolic Demands mentioning
confidence: 99%
“…The protocol was as previously reported with slight modifications. 31,32 Briefly, E17-18 fetuses from the same pregnant Sprague-Dawley rat were used for primary cultures of cortical neurons. Brains were carefully dissected with fine scissors, and cortices were isolated and the meninges were removed with fine forceps in ice-cold DMEM.…”
Section: Primary Rat Cortical Neuron Culturementioning
confidence: 99%
“…Previous studies have reported that GLUT3 is translated by transcriptional factor CREB and Hif-1α. 31,52 Hif-1α is quickly degraded under normoxic conditions and is nearly undetectable. 31 Therefore, CREB protein which also F I G U R E 4 Upregulating GLUT3 increases mPFC glucose uptake and ameliorates depressive-like behaviors of PSD rats.…”
Section: Pka/pcreb Signaling Pathway In Ogd/r Treated Primary Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, both Aβ treatment and tau overexpression inhibit CREB phosphorylation with learning and memory deficits (Yin et al, ). As a transcription factor, CREB‐mediated transcription of BDNF is sufficient to promote neuronal dendrite outgrowth, enhance synapse formation, and improve learning and memory (Bu et al, ; Segarra‐Mondejar et al, ). CREB also mediates the transcription of AMPA receptors, which is the molecular basis of excitatory synaptic transmission (Middei et al, ).…”
Section: Introductionmentioning
confidence: 99%